Steam temperature profiles elapsing from the Laval’ nozzle while fire - Khrustalev Борис; Akel’ev Валерий; Karpenchuk Игорь; Kalinichenko Е.; Maksimov Павел; Kravchuk К.; Kostevich М. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Air and gas streams, elapsing from the Laval’ nozzle to capacity, in fire temperature fields, characterized by high temperatures, thermo dynamical analysis presented. Laval’ nozzle thermo dynamical parameters calculation programme in Pascal ABC programming language elaborated.